Studi Perbandingan Pengaturan Peredaran Kosmetik Antara Badan Pengawas Obat Dan Makanan Republik Indonesia Dengan Food And Drug Administration Amerika Serikat - Nadya Priscilla Wibowo; Rahayu Subekti; Purwono Sungkowo Raharjo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to compare the regulation of cosmetic distribution between the Food and Drug Administration (BPOM) in Indonesia and the Food and Drug Administration (FDA) in the United States. The comparative method is carried out by analyzing regulations, registration procedures, security requirements, post-marketing supervision, and the role of each institution in maintaining the safety of cosmetic products. The research results show that although BPOM and FDA have the same goal of protecting consumers and ensuring the safety of cosmetic products, there are significant differences in their regulatory approaches and registration procedures. BPOM tends to adopt a more formal, qualified approach with strict requirements for registration of cosmetic products, while FDA uses a more flexible approach with more responsibility devolving to manufacturers to ensure compliance with approvals. The two agencies also have differences in post-marketing oversight. Indonesia's BPOM tends to be more active in conducting regular product testing on the market, while the United States FDA relies more on consumer and manufacturer reports to identify unsafe products. However, both face similar challenges in dealing with the rapid development of the cosmetics industry and product innovation. Continuous efforts are needed to improve regulation and supervision to ensure that cosmetic products in circulation are safe for consumers around the world.